Increased myo-inositol in parietal white and gray matter as a biomarker of poor prognosis in neuropsychiatric lupus: a case report. (September 2014) - Guillen-Del Castillo, A; Alonso, J; Martínez-Valle, F; Alonso-Vila, S; Garrido-Castro, AC; Vilardell-Tarrés, M; Rovira, Á; Ordi-Ros, J
Neuropsychiatric manifestations can be a serious complication of systemic lupus erythematosus, affecting nearly 56% of these patients. Frequently, acceptable clinical outcome is observed in neurolupus with immunosuppressive therapy. Different metabolites identified with MR spectroscopy may be associated with modifications in the natural history of this disease, specifically in the central nervous system. We report a case of neurolupus with progressive neurologic impairment despite aggressive immunosuppressive treatment. We describe clinical features, laboratory and MRI results, as well as characteristic findings on MR spectroscopy. Serial MRI identified atrophy of the left temporal lobe. MR spectroscopy showed an increase of myo-inositol/creatine ratio intensity, accompanied by a decrease of N-acetylaspartate/creatine ratio in both parietal white and gray matter. During follow-up, the patient developed progressive cognitive deficiency despite the intensification of therapy. Neurolupus manifestations are common and immunosuppressive treatment often avoids severe complications. Characteristic findings on MR spectroscopy may be useful for clinicians to determine poor prognosis and resistance to therapy.